Social Capital in the Governance of Maspati Village, Surabaya, East Java - Indra Pratama Putra Salmon; Isnaeni Yuliani (Cakrawala, 2026)
The inadequate identification of the local community’s social capital pattern has adversely affected the management of Maspati Village in Surabaya City, which has been operational and emerged as an alternative model for urban tourism villages in Indonesia. In the wake of the pandemic, social capital has continued to weaken as communities have shifted their focus from managing urban tourism villages, which had previously served as a primary source of income, to seeking new economic opportunities in order to survive. This study employed a case study approach, focusing on Maspati Village in Surabaya City as the research object. The informants included the community, stakeholders of the tourism village (managers), as well as MSMEs and home industries. The primary focus centers on the functioning of social capital in the management of urban tourism villages, highlighting the importance of fostering community trust, shared values, and a mutual understanding of common goals. Data were collected through interviews, FGDs, document analysis, and exploration of supporting secondary data. The collected data were further analyzed interactively. The results were validated using triangulation techniques. The findings indicated 1) a decline in community trust, evidenced by a lack of interest in advancing the tourism village due to limited tourist visits and stagnation in local tourism development; 2) a decrease in shared values, particularly in norms that previously attracted tourists; 3) a diminished understanding of initial goals, especially in tourism management, which, albeit fundamentally understood, are now perceived as irrelevant, leading to a lack of adherence to these goals.